The Hospital Sentosa Group Homes Project - Ann, Appleton; David Hi, King Chuong (Universiti Malaysia Sarawak, (UNIMAS), 2014)
In 2003,planningwasinitiatedatHospitalSentosa,Kuching, Sarawak towards providing alternative services for long stay patients, including the identification of suitable housing outside the hospital for selected patients. This move was precipitated by a growing concern about social problems on the wards caused by lack of social support, overcrowding, and the inability to provide adequate programs of care and activity for these patients. In July 2004, nine males were relocated to Bangalow Lada, across the road from Sentosa Hospital and, the following year, twenty nine women were relocated to a renovated building in the grounds of Rajah Charles Brooke Memorial Hospital at 14th mile. Both groups of residents were monitored by staff from the Long Stay wards. This paper assesses the progress of this project in 2009, and includes a discussion of some of the challenges faced, as well as the extent to which the deinstitutionalization process has been successful in human terms. It identifies the service users as primary stakeholders in this process, with the potential to contribute towards the formulation of better policies and ultimately, mental health service transformation.